OFDM signal bandwidth selection for indoor positioning system - Pola, Marek; Bezoušek, Pavel; Škapa, Jiří; Juryca, Karel (IEEE (Institute of Electrical and Electronics Engineers), 2017)
In GPS denied environments like buildings there was unimaginable to wirelessly and electronically track members of rescue squads still few years ago. With today technologies the situation changed but there are still sever challenges to such system. Perhaps the most serious one is a direct signal separation from a bunch of its replicas caused by a multipath propagation. The aim of this article is to assess the problem of accurate direct signal time of arrival measurement in this situation. In the article the model of broadband transmitted and received signals modulated by OFDM are presented and methods of the direct signal delay estimation are described. Later the proper bandwidth for a sub meter accuracy of the range estimation is proposed based on modeling.
Výběr šířky pásma signálu OFDM pro vnitřní polohovací systém
Keywords: RTLS; UWB; OFDM; TDOA; Indoor positioning; RTLS; UWB; OFDM; TDOA; vnitřní určování polohy